Why are Disability Rates for Older Working-Age Adults in Northern Ireland So High? - Devlin, Anne; French, Declan; McVicar, Duncan (The Economic and Social Review, 2023)
Northern Ireland has substantially higher rates of disability and disability benefit receipt than England, despite a common institutional context. This paper exploits newly available data from the NICOLA and ELSA surveys to examine potential health and labour market explanations for this gap, specifically among older working-age people. Observable differences in health and labour markets are sufficient to explain the gap in self-reported activity-limiting disability, but only half of the gap in worklimiting disability and income-replacement disability benefit receipt, and only one-third of the gap in additional costs disability benefit receipt. Possible reasons for these remaining unexplained gaps are discussed.